Determinants Pregnant Women's Use of Maternal and Child Health (MCH) Books at Puskesmas Paal Merah II, Jambi City in 2024 - Azizah, Fitri; Asparian, Asparian; Hubaybah, Hubaybah; Sari, Rumita Ena; Siregar, Sri Astuti (PT. Anagata Sembagi Education, 2025)
The health of mothers and children is of utmost importance in health development in Indonesia, with the aim of reducing rates of infant mortality (IMR) and maternal mortality (MMR). Using the Maternal and child Health Book (KIA) in Antenatal Care services is one of the government’s initiatives. Puskesmas Paal Merah II Jambi City is still low in the utilization of the MCH book 23.4%. The purpose of this study is to identify the variables linked to the utilization of the MCH book among In 2024, pregnant women at Jambi City's Paal Merah II Health Center. This study uses a cross-sectional approach and is quantitative in nature. The population in this study were 407 pregnant women a sample size of 79 respondents. The analysis test used was the chi-square test (95% CI). With a p-value of 1,000, there is no correlation between age and the use of the Maternal and Child Health (MCH) book. With a p-value of 0.337, there is no correlation between education and the use of MCH books. Knowledge and the use of the MCH book are related, as indicated by the p-value of 0.000. The availability of Human Resources (HR) and the use of MCH books are related, as indicated by the p-value of 0.025. A p-value of 1,000 indicates that there is no correlation between the use of the MCH book and individual evaluation.